Clinical and genetic characteristics of PSTPIP1-associated myeloid-related proteinemia inflammatory syndrome - Dan Zhang; Gaixiu Su; Yan Liu; Jianming Lai (BMC, 2021)
Abstract Objective To summarise the clinical and genetic characteristics of three children with PSTPIP1-associated myeloid-related proteinemia inflammatory (PAMI) syndrome. Methods This study retrospectively analysed the clinical and genetic data of three children with PAMI syndrome in our hospital between April 2018 and January 2020. Results One male and two female children were 6 years and 5 months, 8 years and 7 months, and 13 years and 3 months of age. All three patients had a recurrent blood trilineage hypoplasia and splenomegaly. Patient 1 had pyoderma gangrenosum, and Ludwig's angina. Patient 2 had pyogenic arthritis, and pyoderma gangrenosum. Patient 3 had hepatomegaly, pyogenic arthritis, and pulmonary hypertension. Laboratory tests revealed that all three children had elevated C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR). Patient 1: C-antineutrophilic cytoplasmic antibodies(c-ANCA), positive; antiglobulin test (Coombs), positive. Patient 2: blood zinc, 4.38 mg/L (elevated). Patient 3: Antinuclear antibodies (ANA), 1:100, β2 glycoprotein I, positive; Coombs test, positive; RF, 28.3 U/ml (elevated); C3, 0.77 g/L (decreased). Genetic testing showed that all 3 patients had PSTPIP1 c.748G > A (p.E250K) spontaneous heterozygous mutations, suggesting the diagnosis of PAMI syndrome. Patient 1 was treated with a combination of methylprednisolone and cyclosporine for 8 months. The patient did not develop new skin lesions. The blood count showed mild neutropenia. The spleen was considerably retracted and the CRP became normal. Patient 2 was treated with etanercept and methylprednisolone. The patient had no further arthralgias and pyoderma gangrenosum showed improvement. The spleen was smaller than before. White blood cells were shown to be approximately 2-3 × 109/L. The haematocrit, platelets, CRP, and AESR were normal. Patient 3 was treated with methylprednisolone, methotrexate, and infliximab 4 times. The patient's joint symptoms disappeared gradually and the liver retracted markedly. The pulmonary artery pressure returned to normal. Moreover, Coombs test result was negative. CRP and AESR were lower than before. Conclusion PAMI syndrome can manifest as pyogenic arthritis, pyoderma gangrenosum, acne, and trilineage hypoplasia, as well as autoimmune diseases. Glucocorticoid and immunosuppressive therapy are partially effective and cytokine antagonists can be used in refractory cases. Whole-exome genetic testing is helpful to confirm diagnosis.